Relation- and Task-Oriented Roles as Antecedents of Ethical Leadership: Examining Synergistic Effects - H. M. Saidur Rahaman (Europe's Journal of Psychology)
A growing body of literature demonstrates that ethical leadership has positive effects on employees’ work outcomes. Ethical leadership upholds the importance of “normatively appropriate conduct through personal actions and interpersonal relationships” (Brown et al., 2005, p. 120; doi:10.1016/j.obhdp.2005.03.002). However, extant empirical research does not answer the question- of how ethical leaders balance their relation maintenance (i.e., relationship-oriented role) and performance maintenance (i.e., task-oriented role) behaviors with their employees to be perceived as ethical leaders. In the present paper, drawing upon the propositions informed by opposing domains theory and related research, I theorize that leaders’ relationship-oriented and task-oriented roles create synergistic effects that predict their employees’ perceptions of ethical leadership. Results across two studies (an experiment and a correlational study involving samples from two different cultures) convergently confirmed the hypothesized relationships. I conclude by discussing several key theoretical and practical implications of these findings.